Influence of advanced cylinder coatings on vehicular fuel economy and emissions in piston compression ring conjunction. (1st February 2020) - Dolatabadi, N.; Forder, M.; Morris, N.; Rahmani, R.; Rahnejat, H.; Howell-Smith, S.
Highlights: A multi-physics, multi-scale model evaluates engine component power loss. Effect of advanced coatings on energy efficiency and emissions is evaluated. The potential global implications of using advanced coatings is highlighted. Abstract: IC engines contribute to global warming through extensive use of fossil fuel energy and emission of combustion by-products. Innovative technologies such as cylinder de-activation (CDA), after-exhaust heat treatment, surface texturing and coatings are proposed to improve fuel economy and reduce emissions of the vehicle fleet. Therefore, study of coating technology through a comprehensive multi-physics analytical model of engine top compression ring is important to ascertain ways of promoting energy savings. This paper presents a multi-scale, multi-physics model of the compression ring-cylinder bore conjunction, using three alternative bore surfaces. The model comprises ring dynamics, contact tribology, heat transfer and gas blow-by. Tribological and thermal properties of advanced coatings, such as Nickel Nanocomposite (NNC) and diamond-like carbon (DLC) are compared with an uncoated steel bore surface as the base line configuration. Such a comprehensive analysis has not hitherto been reported in open literature, particularly with original contributions made through inclusion of salient properties of alternative bore materials for high performance race engines. Power loss and FMEP are evaluated in a dynamometric test, representative of the World-wide harmonised Light vehicles Test Cycle (WLTC). The NNC coating shows promising tribological improvements. The DLC coating is detrimental in terms of frictional power loss and FMEP, although it can effectively improve sealing of the combustion chamber. The differences in power loss of nominated bore surfaces are represented as fuel mass and CO emissions, using theoretical and empirical relations. For the first time the paper shows that advanced coatings can potentially mitigate the adverse environmental impacts of spark ignition (SI) engines, with significant repercussions when applied to the global gasoline-powered vehicle fleet.